2005
DOI: 10.1093/hmg/ddi129
|View full text |Cite
|
Sign up to set email alerts
|

RPGR ORF15 isoform co-localizes with RPGRIP1 at centrioles and basal bodies and interacts with nucleophosmin

Abstract: The ORF15 isoform of RPGR (RPGR(ORF15)) and RPGR interacting protein 1 (RPGRIP1) are mutated in a variety of retinal dystrophies but their functions are poorly understood. Here, we show that in cultured mammalian cells both RPGR(ORF15) and RPGRIP1 localize to centrioles. These localizations are resistant to the microtubule destabilizing drug nocodazole and persist throughout the cell cycle. RPGR and RPGRIP1 also co-localize at basal bodies in cells with primary cilia. The C-terminal (C2) domain of RPGR(ORF15) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 51 publications
5
90
0
Order By: Relevance
“…The distinct partitioning of a subset of RPGRIP1 isoforms between the nuclear and cytoplasmic compartments combined with the differential and limited proteolysis of RPGRIP1 among retinal neurons, and the impact of LCA-linked mutations in RPGRIP1 in these processes, support the involvement of nucleocytoplasmatic signaling processes mediated by RPGRIP1 and its interacting partners in the pathogenesis of LCA, RP3, and allied diseases (15,16). The presence of both RPGR and RPGRIP1 proteins in basal bodies and centrosomes of cultured dividing, but not interphase mammalian cells of nonretinal origin, suggests also a pleiotropic function of this protein complex (17). The absence of an RPGRIP1 isoform in Rpgrip1 Ϫ/Ϫ mutant mice appears to lead to a defect in outer segment disk formation, suggesting a role in disk morphogenesis (18).…”
mentioning
confidence: 71%
“…The distinct partitioning of a subset of RPGRIP1 isoforms between the nuclear and cytoplasmic compartments combined with the differential and limited proteolysis of RPGRIP1 among retinal neurons, and the impact of LCA-linked mutations in RPGRIP1 in these processes, support the involvement of nucleocytoplasmatic signaling processes mediated by RPGRIP1 and its interacting partners in the pathogenesis of LCA, RP3, and allied diseases (15,16). The presence of both RPGR and RPGRIP1 proteins in basal bodies and centrosomes of cultured dividing, but not interphase mammalian cells of nonretinal origin, suggests also a pleiotropic function of this protein complex (17). The absence of an RPGRIP1 isoform in Rpgrip1 Ϫ/Ϫ mutant mice appears to lead to a defect in outer segment disk formation, suggesting a role in disk morphogenesis (18).…”
mentioning
confidence: 71%
“…RPGR has a complex splicing pattern with multiple tissue-and cell-specific isoforms (52), is known to interact with a number of ciliary proteins (53,54), acts as a gunanine nucleotide exchange factor for small GTPase RAB8A (55), and may have a role in vertebrate development (56). Such complexity may account partially for the variability in disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Selective entry through the nuclear pore requires cargo binding to a GTPbinding protein and guanine-nucleotide exchange involving a GEF to release cargo into the nucleus (27). We showed that RPGR ORF15 , a putative GEF (28), is a cilia/centrosomal protein that may regulate selective transport of cargo proteins from basal bodies distally along the ciliary axoneme in the photoreceptor connecting cilium (14,29). We now show that RPGR ORF15 is in complex with CEP290 in OSNs of both WT and rd16 mice, suggesting a possible role in regulating protein entry into the olfactory cilium.…”
Section: Discussionmentioning
confidence: 99%